Sodobne slovenske dramske pisave in družbenoangažirane uprizoritvene prakse - Murnik, Maja (Primerjalna književnost, 2019)
The article is based on the assumption that in the last decade it has no longer been adequate to strictly distinguish drama from theatre as we are dealing with "no-longer-dramatic" theatre texts (Poschmann) and with "postdramatic" theatre (Lehmann). The crisis of representation and of the drama form has introduced heterogeneous, performative and open structures. They reflect the altered position and status of today's art whose modern autonomy has dissolved, while art itself has begun to appropriate other procedures and functions. The paper examines several plays by Simona Semenič as well as several politically-shaped and activist examples of contemporary performing arts in Slovenia where the textual part takes on a significant role (Metamorphoses 4: Black Holes by B. Kolenc, The Republic of Slovenia and Odilo. Obscuration. Oratorio by D. Živadinov). These texts range from simple political agitation plays to complex examinations of social and political issues.
Keywords: družbeni angažma; Kolenc, Bara; politično gledališče; postdramsko gledališče; Semenič, Simona; sodobna slovenska dramatika; umetnost in politika; uprizoritvene prakse; Živadinov, Dragan